Synthesis of Highly Uniform Mo-glycerate Spheres and Their Conversion to Hierarchical MoS2 Hollow Nanospheres for Lithium-Ion Batteries - Wang, Yawen (2016)
Highly uniform Mo–glycerate solid spheres are synthesized for the first time through a solvothermal process. The size of these Mo–glycerate spheres can be easily controlled in the range of 400–1000 nm by varying the water content in the mixed solvent. As a precursor, these Mo–glycerate solid spheres can be converted into hierarchical MoS2 hollow nanospheres through a subsequent sulfidation reaction. Owing to the unique ultrathin subunits and hollow interior, the as-prepared MoS2 hollow nanospheres exhibit appealing performance as the anode material for lithium-ion batteries. Impressively, these hierarchical structures deliver a high capacity of about 1100 mAh g−1 at 0.5 A g−1 with good rate retention and long cycle life.